Computer game prototypes developed around food security and climate change - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
Prototype games were developed into working games - and tested with key audiences throughout multiple iterations during the development process, leading to new prototypes, finally published on Itch.io.